Hepatic transcriptomic responses in gravid and non-gravid rats exposed to HFPO-DA: Analyses to inform the role of maternal effects in neonatal toxicity - Melissa M. Heintz; Chad M. Thompson; Jeffrey C. Wolf; John M. Rogers; Laurie C. Haws (PLoS ONE, 2026)
Like many per- and polyfluoroalkyl substances (PFAS), toxicity studies for short-chain HFPO-DA (ammonium, 2,3,3,3-tetrafluoro-2-(heptafluoropropoxy)-propanoate) indicate the liver is the primary target of toxicity in rodents. However, neonatal mortality and decreased birth weight have also been reported in rats following oral exposure to HFPO-DA in utero . Additional exposure-related effects in neonatal rats included hypoglycemia, decreased liver glycogen, and perturbed hepatic expression of genes related to glucose metabolism and peroxisome proliferator activated receptor (PPAR) signaling. A putative rodent-specific adverse outcome pathway (AOP) network was recently developed using these endpoints and assessed for its applicability to PFAS. AOP 1 in this putative AOP network consists of PPARα activation as one of multiple initiating events, with placental insufficiency, neonatal hepatic glycogen deficit, and hypoglycemia as key events leading to neonatal mortality and lower birth weight. To further inform AOP 1 and investigate whether this altered carbohydrate metabolism liver phenotype observed in rat neonates also occurs in HFPO-DA-exposed gravid and non-gravid adult rats, transcriptomic analysis and glycogen staining were performed on archived female rat liver samples from a 15-d developmental and 90-d subchronic toxicity study. HFPO-DA-mediated changes in hepatic gene expression in adult female rats were consistent with PPARa signaling. Changes in hepatic glycogen content and glucose metabolism-related gene expression did not appear to be dependent on HFPO-DA exposure, suggesting that the altered carbohydrate metabolism phenotype observed in neonatal rat livers is not likely to occur in adult female rats, regardless of pregnancy status. Therefore, key events in this AOP for neonatal mortality and lower birthweight are likely limited to the placenta and/or perinatal rat and are unlikely to be secondary to changes in carbohydrate metabolism in maternal liver. Additionally, findings from this study are consistent with previous mechanistic studies supporting the rodent-specific PPARα mode of action for HFPO-DA-mediated liver effects in rodents.